Is There a Role for Post-Mastectomy Radiotherapy for T1-2N1 Breast Cancers With Node-Positive Pathology After Patients Become Node-Negative Pathology Following Neoadjuvant Chemotherapy? - Wang, Qian; Zhao, Jingjing; Han, Xiaowei; Er, Puchun; Meng, Xiangying; Shi, Jinyan; Sun, Huiru; Zhu, Jingyang; Zhu, Li; Wu, Shikai; Zhang, Wencheng; Sun, Bing (Frontiers in Oncology, 2020)
Purpose: To assess the benefit of post-mastectomy radiotherapy (PMRT) in breast cancer (BC) patients with T1-2N1M0 who developed pathologically negative lymph nodes (ypN0) after undergoing neoadjuvant chemotherapy (NAC) and mastectomy. Patients and Materials: Patients with T1-2 tumors and positive lymph node(s) who became pN0 after NAC and mastectomy were screened from our prospectively maintained database. The primary endpoint was recurrence-free survival (RFS), and the secondary endpoints were local recurrence-free survival (LRFS) and overall survival (OS). Propensity-score matching (PSM) was conducted for the comparison between PMRT and non-PMRT groups. Results: Of the 142 eligible patients, 110 (77.5%) received PMRT, and 32 (22.5%) did not. The median follow-up time was 72 months. Univariate analyses showed that the 5-year RFS, LRFS, and OS rates were 88.7%, 94.5%, and 96.1%, respectively, with PMRT and 72.4%, 90.1%, and 95.0% without PMRT (p = 0.028; p = 0.151; p = 0.971). Multivariate analyses established PMRT as a significant prognostic factor for RFS rate (HR, 0.411; 95%CI, 0.175-0.968; p = 0.042). After a PSM analysis (64 in the PMRT group vs. 32 in the non-PMRT group), PMRT remained significant, with improved RFS in univariate and multivariate analysis (with 5-year RFS rates of 90.1% vs. 72.7%, respectively, p = 0.016; HR, 0.321, 95%CI, 0.114-0.904, p = 0.031). In the subgroup of 48 (33.8%) patients with pathologic complete responses (pCR, ypT0 and ypN0) after NAC, PMRT did not affect RFS (HR, 0.226; 95%CI, 0.034-1.500; p = 0.123). Conclusions: PMRT might benefit pT1-2N1M0 patients with pN0 after NAC. Patients with pCR might consider omitting PMRT. Prospective studies are needed to assess the effect of PMRT on this specific patient population.